The relation between maximal voluntary force in m. palmaris longus and the temporal and spatial summation of muscle fiber recruitment in human subjects. Issue 1 (15th January 2018) - Claudel, Cécyl G.; Ahmed, Waqas; Elbrønd, Vibeke S.; Harrison, Adrian P.; Bartels, Else Marie
Abstract: This study aimed at looking at the frequency (T‐score) and the amplitude (S‐score) of fiber use during contraction of a forearm muscle, m. palmaris longus, as measured by acoustic myography (AMG). An additional aim was to relate the T‐ and S‐scores to the recorded force obtained from a hand dynamometer. The hypothesis being that temporal and spatial summation of muscle fiber contraction in a given muscle during a given movement, can together describe a given obtained force. Force measurements were carried out on 12 healthy human subjects aged 19–68 years (6 men & 6 women), while their m. palmaris longus contractile function was measured using an acoustic myography CURO device. Force production was varied from 90 to 10% of assessed maximal voluntary force (MVF), and also monitored over a 1 min period of 50% MVF. Linear regression analysis was applied to relate force to spatial and temporal summation. Muscle strength was sustained by changing the frequency and/or the number of active fibere at any given point in time. Force production, whilst stronger for men than women, was regulated in a similar fashion for both sexes and was closely correlated with the AMG T‐ and S‐scores. It is concluded that AMG is a noninvasive method which can be readily applied to accurately describe how a subject uses a given muscle during any given movement. These findings have relevance when considering training strategies in subjects with muscle trauma or disease, in the elderly, or for both amateur and top professional athletes. Abstract : Acoustic Myography is a noninvasive method which can be readily applied to accurately describe how a subject uses a given muscle during any given movement. Force production, whilst stronger for men than women, was regulated in a similar fashion for both sexes and was closely correlated with the Acoustic Myography Temporal– and Spatial summation–scores. These findings have relevance when considering training strategies in subjects with muscle trauma or disease, in the elderly, or for both amateur and top professional athletes.